Մովսես Խորենացու ծննդյան վայրի հարցի շուրջ - Ղազարյան, Աստղիկ (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
Elucidation of the problems connected with Movses Khorenatsi’s biography is important for historiograhy. One of them is the issue of the birth place of the Father of Armenian historiography. Освещение проблем, связанных с биографией Мовсеса Хоренаци (V в.), важно для историографии. Одним из них является вопрос о времени и месте рождения Отца армянской историографии.
Keywords: Հայ պատմագրություն; Պատմագիտություն; Հայագիտություն; Կենսագրություն